Unravelling the chemodiversity of eggplants - Insight into their role in the underlying response to biotic and abiotic stresses - Subramanian, Meenakshi; Ramesha, Nikhil Kumar; Abhiram, KP; Kumar, Manoj; Vismaya, Pattantavida; Vanishree, Srinivasamurthy; Likitha Aishwarya, HS; Udupa, Srivatsa; Shivappa, Swathi; Swathy, Puthanvila Surendrababu; Thorat, Sachin Ashok; Kaniyassery, Arya; et al. (Frontiers in Plant Science, 2026)
Solanum melongena L. is a significant annual vegetable crop belonging to the Solanaceae family. It is cultivated worldwide, particularly in tropical and subtropical regions. It is rich in proteins and dietary fibres and contributes to its broad range of secondary metabolites, thereby increasing its chemodiversity. Secondary metabolites like phenolics, terpenoids, glycoalkaloids, flavonoids, and antioxidants act as stress regulators. While eggplant is known for its phytochemical profile associated with nutraceutical properties, the role of its chemodiversity in conferring tolerance to stresses remains underexplored. Therefore, understanding the chemodiversity of eggplant is crucial for developing stress-resistant cultivars. This approach addresses a critical gap by linking chemodiversity with adaptive responses and offers new perspectives for crop improvement. Currently, researchers are widely using metabolomics, high-throughput analytical tools and bioinformatic tools to evaluate chemodiversity in different parts of plants. Large-scale characterization of the phytochemical diversity of eggplant genotypes under various stress conditions has been performed via high-throughput screening techniques. Understanding the regulatory network and biochemical pathways involved in stress adaptation in eggplant can be accomplished by integrating metabolomics, genomics, and transcriptomics. Overall, this review discusses the importance of chemodiversity in eggplant during stress conditions by highlighting the chemical and metabolic diversity of different eggplant cultivars and their wild relatives, emphasizing their functional roles in plant defense and stress adaptation.